2015
DOI: 10.1002/hpm.2309
|View full text |Cite
|
Sign up to set email alerts
|

An alternative way of understanding exit, voice and loyalty: the case of informal payments for health care in Israel

Abstract: This study examines Hirschman's model of exit, voice and loyalty with regard to informal payments in the Israeli healthcare system. Based on a national survey, we investigate the extent of "black" payments, its characteristics and its correlated factors. We find that informal payments do exist in Israel-although it seems that there has been a decline in the phenomenon. Contrary to the literature, we find no relationship between the option of voice or dissatisfaction with healthcare services and informal paymen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Diverse ranges of objectives and scopes, research methods and results have been reported in this regard. A number of these studies have focused on the views and attitudes of patients and service providers toward IPs in health system [13,17,[32][33][34][35][36][37][38][39][40], and a few of them have measured the impact of IPs on the health economy with respect to goals and indicators [41][42][43][44][45]. Several studies have focused on the definitions and methods of studying IPs and systematic reviews in this area [9,[46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…Diverse ranges of objectives and scopes, research methods and results have been reported in this regard. A number of these studies have focused on the views and attitudes of patients and service providers toward IPs in health system [13,17,[32][33][34][35][36][37][38][39][40], and a few of them have measured the impact of IPs on the health economy with respect to goals and indicators [41][42][43][44][45]. Several studies have focused on the definitions and methods of studying IPs and systematic reviews in this area [9,[46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable to assume that citizens' lack of trust will be related to their perceptions about the health care system and their willingness to make informal payments for health care. Indeed, Filc and Cohen (2015) and Cohen and Filc (2017) has established such a link in Israel.…”
Section: Israeli Citizens' Attitudes and The Health Care Systemmentioning
confidence: 99%
“…First, exit and voice are often linked to expressions of citizenship (Lyons et al 1992), and, in general, the current literature tends to approach the four optional EVLN responses to dissatisfaction as legitimate and consistent with existing provision arrangements. Second, responses to dissatisfaction that exemplify inconsistency with current provision arrangements often refer to the creation and establishment of an alternative supply, which takes place outside the formal supply of the service (Lehman‐Wilzig 1991), and only rarely to behaviours that manipulate existing arrangements (e.g., Cohen and Filc 2017). Third, gaming has been identified as a behaviour of bureaucrats and of targets of regulation; however, it has not been systematically identified as a behaviour of public service clients.…”
Section: Gaming Response To Dissatisfaction With Public Servicesmentioning
confidence: 99%
“…One prominent example in which gaming and alternative politics overlap is the well‐documented phenomenon of informal payments in healthcare, where alternative politics takes the form of ‘payments to individuals and institutional providers, in kind or in cash, that are made outside official payment channels and purchases that are meant to be covered by the healthcare system’ (Cohen 2012, p. 287, see also Cohen and Filc 2017). Such payments aim at improving the outcome of a healthcare service through, for instance, earlier appointments, obtaining medication unofficially or the ability to choose a doctor.…”
Section: Gaming Response To Dissatisfaction With Public Servicesmentioning
confidence: 99%